Will the miniaturization of household size promote household carbon emissions in China? Analysis based on CFPS data - Shao, Hongmei; Yu, Meifeng; Xia, Mengjie; Yu, Dan; Gao, Fuyang (Frontiers in Environmental Science, 2024)
Abstract：As the proportion of household carbon emissions to global carbon emissions continues to increase, reducing carbon emissions from household consumption has become an important way to achieve the goals of carbon peaking and carbon neutrality. How the trend of miniaturization of household size will affect household carbon emissions is a matter of concern. This paper uses a sample of 9090 households from the China Family Panel Survey (CFPS) database in 2018 to empirically study the impact of changes in household size on household carbon emissions, from the perspective of household consumption structure and urban-rural areas. The research results indicate that the miniaturization of household size will increase household carbon emissions, the impact of household size on indirect HCEs is greater than on direct HCEs. The impact of household size on indirect HCEs is heterogeneous in consumption structure and the impact of household size on indirect HCEs from housing, transportation is greater than that of other consumption items. The impact of household size on urban household carbon emissions is greater than that in rural areas. The upgrading of household consumption structure and the miniaturization of household size promote the increase HCEs. Therefore, this paper proposes that under the trend of household miniaturization, energy-saving and emission reduction policies should focus on reducing indirect households carbon emissions, optimizing household structure and household consumption structure, enhancing environmental awareness among family members, establishing a sound green consumption system, and building environmentally friendly households. Keywords ： household carbon emissions, household size, indirect household carbon emissions，household consumption structure, the CFPS data